PENDAMPINGAN PENGGUNAAN APLIKASI SKETCHUP DAN V-RAY PADA SMK TARUNA PEKANBARU - Samra, Boby; Rizal, Yose; Silva, Hendri (Komunitas Manajemen Kompetitif, 2024)
The mentoring socialization activity at SMK Taruna Pekanbaru is part of the Tri Dharma activities of higher education carried out by the Lancang Kuning University Architecture study program lecturer service team. Assistance is carried out to increase the knowledge of vocational students in the development of digital drawing technology using applications, so that students can get additional experience in facing the business world and the industrial world. It is expected that SMK students when they enter the world of work are ready with digital drawing skills. With this implementation, students can prepare themselves early and measurably in order to face the future challenges of the digital drawing world.